An innovative approach for storing berries in the modern - Kiurchev, Serhii; Кюрчев, Сергій Володимирович; Кюрчев, Сергей Владимирович; Glowacki, S.; Verkholantseva, Valentyna; Верхоланцева, Валентина Олександрівна; Верхоланцева, Валентина Александровна (ТДАТУ, 2020)
Freezing is one of the most promising methods of canning. In frozen products better than in canned in any other way, the main components that determine the nutritional value are preserved. According to organoleptic indicators - taste, aroma, color, appearance of frozen products are little different from fresh. The most effective is the use of canning by freezing for processing fruits and vegetables. The most effective fast freezing at a temperature of (- 30 °C) and below.
Keywords: storage of raw materials; storage period; freezing; the pressure